2003
DOI: 10.1046/j.1365-2125.2003.01875.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions in elderly patients

Abstract: Many studies from around the world show a correlation between increasing age and adverse drug reaction (ADR) rate, at least for some medical conditions. More than 80% of ADRs causing admission or occurring in hospital are type A (dose-related) in nature, and thus predictable from the known pharmacolog y of the drug and therefore potentially avoidable. Frail elderly patients appear to be particularly at risk of ADRs and this group is also likely to be receiving several medicines. The toxicity of some drug combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
263
3
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 401 publications
(290 citation statements)
references
References 53 publications
(51 reference statements)
8
263
3
11
Order By: Relevance
“…ADRs due to drug-drug interactions are a common cause of admission to the hospital and are an important cause of mortality and morbidity. Studies done after 1985 have shown that the ADR rate in European and American geriatric settings are greater by at least 20% when compared to the general medicine setting [17] . Another 4-y prospective study done among geriatric residents of nursing homes from USA has reported that the mean number of drugs per patient in the ADR group was 7.8 while the mean number of drugs in the remaining geriatric population was a mere 3.3 [18] .…”
Section: Resultsmentioning
confidence: 99%
“…ADRs due to drug-drug interactions are a common cause of admission to the hospital and are an important cause of mortality and morbidity. Studies done after 1985 have shown that the ADR rate in European and American geriatric settings are greater by at least 20% when compared to the general medicine setting [17] . Another 4-y prospective study done among geriatric residents of nursing homes from USA has reported that the mean number of drugs per patient in the ADR group was 7.8 while the mean number of drugs in the remaining geriatric population was a mere 3.3 [18] .…”
Section: Resultsmentioning
confidence: 99%
“…However, older adults are at higher risk of adverse drug reactions (ADR) due to age-related pharmacokinetic and pharmacodynamic changes and polypharmacy (1). They are also more susceptible to non-adherence and to practical difficulties with medication taking such as cognitive impairment and various functional problems (2).…”
Section: Introductionmentioning
confidence: 99%
“…The increased number of medications used by a patient correlates with poorer compliance, increased risk of drug-drug interactions and adverse drug reactions (ADRs) and increased economic burden [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%